Intellectual Property Rights for Tourism Potential in Alamendah Village, Rancabali District, Bandung Regency - Nurrachmi, Intan; Imaniyati, Neni Sri; Jamilah, Lina; Respati, Titik; Nugraha, N; Alamsyah, Indra Fajar; Hadi, Abdul Razak bin Abdul (KnE Social Sciences, 2024)
Alamendah Village is located in Rancabali District, Bandung Regency, West Java. This village is one of the most sophisticated agronomy villages in Rancabali District, which is also known as natural tourism, religious tourism, and agricultural tourism. With a geographical location in the form of hills or highlands, the agricultural sector is the most prominent economic activity in Alamendah Village, hence most of the people’s livelihoods are farming and trading. This village was chosen as the site by LPPM Unisba in collaboration with Universiti Kuala Lumpur (UniKL), one of the prestigious private universities in Malaysia, which focuses on developing rural areas, for conducting community service regarding village development model. The methodology used in this activity was training for business actors in Alamendah Village through lectures, discussions, questions and answers, pre-test and post-test, providing mentoring assistance, and submitting IPR. The result is Alamendah tourism village has enormous tourism potential in the fields of nature tourism, religious tourism, and agro-tourism. Community service activities in Alamendah Village have increased awareness and knowledge about the importance of intellectual property rights in their business. Keywords: Alamendah Village, intellectual property rights, tourism